Distance Education for all Ages in Romania - Elena-Maria Emandi (Association of Social and Educational Innovation, 2017)
Both society as a whole and each of its members have to be prepared for the changes caused by continuous evolvement of knowledge. Alongside with the traditional forms of education, distance education represents the chance people of all ages have to learn in order to have a better chance to adapt to the ever-changing society.